The Ethanol Extract Fractionation (Peperomia Pellucida (L.) Kunth) On Uric Acid Levels Blood Serum Of Male White Mice - Hevira, Linda; Yulion Putra, Rizky; Suciati, Rahma Anggun (JURNAL FARMASI GALENIKA, 2023)
Research has been carried out on the effect of fractionating the ethanol extract of the messenger herbs (Peperomia pellucida (L.) Kunth) to reduce blood serum uric acid levels in male white mice. Ordered herbs containing flavonoid compounds are thought to be used as lowering uric acid levels in the blood. The purpose of this study was to determine the effect of giving the ethanol extract fraction (Peperomia pellucida (L.) Kunth) on blood serum uric acid levels of male white mice. Simplicia extraction was carried out with 96% ethanol and extract fractionation was carried out using n-hexane, ethyl acetate, and water as solvents. The chicken liver inductor was used using experimental methods in vivo. Uric acid levels in mice were measured using a test-strip out. The results of the analysis using statistical tests on the decrease in uric acid levels in the blood were significant with a value (p 0.05) on the 14th day of the ethyl acetate fraction. This study concludes that there are compounds in the messenger herbs that have the potential to reduce uric acid levels in the blood.